FIELD PERFORMANCE AND ADAPTATION OF NEW EARLY MATURING MULTIPLE STRESS TOLERANT PRO-VITAMIN A MAIZE (Zea mays L.) HYBRID TO THE DERIVED SAVANNA AGRO-ECOLOGY OF NIGERIA - Kolawole, Adesike; Raji , Ibrahim; Oyekale, Solomon (Journal of Agricultural Sciences (Belgrade), 2021)
Maize (Zea mays L.) is a staple food for millions of people across the globe and it supplies more than 30 % of total dietary calories. However the normal endosperm lacks sufficient quantity of the nutritive precursor of vitamin A. To achieve food security and avert malnutrition, there is a need to adopt the cultivation of early multiple stress tolerant pro-vitamin A maize hybrid. The objective of this study was to assess the agronomic performance and yield of the newly developed maize hybrids. Fifteen maize hybrids plus one commercial check were evaluated in a randomized complete block design with two replications for two years at the Ladoke Akintola University of Technology Teaching and Research farm in Ogbomoso, Nigeria. Hybrids exhibited significant variation (P < 0.01) for only grain yield, number of days to anthesis and silking, ear height and husk cover. Across the years, grain yield of hybrids ranged between 4,780.8 and 7,886.9 kg ha−1 with mean of 6,354.2 kg ha−1. PVAEH-15 ranks best on the basis of superiority in grain yield, early flowering and tight husk cover. Fourteen hybrids out-yielded the local check (4947.2 kg ha-1) and five hybrids had a significant (P < 0.05) yield advantage of > 26 % over the local check. The consistent performance of PVAEH-15 and PVAEH-16 in the two years of evaluation indicates adaptability of the hybrids to the agro-ecology. Farmers’ adoption of these maize hybrids will boost maize production and prevent malnutrition in the derived savanna agro-ecology of Nigeria.
Keywords: evaluation, flowering, food security, grain yield, malnutrition.